Does it pay off to smile even it is not authentic? Customers' involvement and the effectiveness of authentic emotional displays - Stephan Olk; Dieter K. Tscheulin; Jörg Lindenmeier (Marketing Letters, 2021)
Research has shown that while the authenticity of positive emotional displays plays an important role in service encounters, it has not yet demonstrated a universally positive effect on customers' behavior. This study, which is the first to present customer involvement as a contextual factor that influences customers' processing, provides a deeper understanding of the effectiveness of the authenticity of emotional displays. The model is based on expectation disconfirmation theory and emotional contagion theory and is validated in a field experiment and two laboratory experiments that use video stimuli with actors in real-world contexts. The results show that even inauthentic displays can meet customers' expectations depending on their involvement and that high-involvement customers adapt to employees' authentic emotions more strongly than low-involvement customers do. In summary, the presented model strengthens the understanding of the role of authentic displays and provides an approach to improve the effectiveness of emotional labor strategies.
Keywords: 380; Emotional labor; Authenticity; Customer involvement; Cognitive and affective processing